Dynamic Covalent Chemistry within Biphenyl Scaffolds: Effects from Endocyclic to Exocyclic Sulfonamides - Ni, Cailing; Wang, Meng; You, Lei (Synlett, 2018)
There is unabated interest in developing new strategies for the control of atropisomers despite the rich history of atropisomerism. We recently introduced dynamic covalent reactions (DCRs) within biphenyl skeletons for the incorporation and chirality recognition of multiple classes of mononucleophiles. To expand the scope of this strategy, the sulfonamide unit was switched from an endocyclic to an exocyclic position, and the influence of the resulting DCRs on chiral induction was investigated. The intramolecular equilibrium between the open aldehyde and its cyclic hemiaminal favored the ring form, and excellent chirality transfer from the hemiaminal stereocenter to the helical twist of the biphenyl was revealed. The modulation of unique dual reactivity then allowed the realization of DCRs of a diverse set of amines and alcohols. The degree of chirality induction was further explored by employing chiral substrates, affording significant circular dichroism signals.
Keywords: atropisomerism; biaryls; aldehydes; dynamic covalent chemistry; chirality recognition